2006
DOI: 10.1111/j.1365-2621.2006.tb08900.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electron Beam Irradiation on Physical, Textural, and Microstructural Properties of “Tommy Atkins” Mangoes (Mangifera indica L.)

Abstract: This research focused on determining the dose levels suitable for electron beam irradiation of mangoes without detriment to the fruit's quality characteristics. Physicochemical, textural, respiration rates, microstructural, and sensory characteristics of “Tommy Atkins” mangoes irradiated at 1.0, 1.5, and 3.1 kGy using a 10 MeV (10 kW) linear accelerator with double‐beam fixture were determined. Fruits were stored at 12 °C and 62.7% RH for 21 d and evaluated at days 0, 5, 10, and 21. Nonirradiated mangoes serve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
31
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 20 publications
10
31
0
Order By: Relevance
“…The possible reasons may be that medium to lower dose of irradiation can break chemical bonds, increase membrane permeability and metabolic activity, which will lead to more water vapor movement to intercellular space and maintain the texture of the fruit and another reason may be that the changes in pectin by irradiation are possible cause of the radiation induced softening (Zhao et al 1996). These results are in agreement with findings of Moreno et al (2006), El-Salhy et al (2006) and Lacroix et al (1990) in mango; Pimentel and Walder (2004) in banana and Singh and Pal (2007) and Singh and Pal (2009) in guava. Significantly better texture score was recorded at the full ripening stage in fruits stored at 12 0 C, ambient temperature and in CA (12 0 C) storage compared to fruits stored at 9 0 C temperature, which may be due to retardation of the biochemical changes and ripening process at desired temperature (Mane, 2009) and significantly decrease in texture during storage of fruits was due to changes in nature of pectin substances which cementing the cell wall and hydrolysis of starch, hemicelluloses and cellulose during ripening of fruit (Leopold, 1964).This finding is in conformity with the findings of Waskar and Masalkar (1997) in mango; Purvoko (2002) in banana.…”
Section: Texture Of Fruitsupporting
confidence: 88%
“…The possible reasons may be that medium to lower dose of irradiation can break chemical bonds, increase membrane permeability and metabolic activity, which will lead to more water vapor movement to intercellular space and maintain the texture of the fruit and another reason may be that the changes in pectin by irradiation are possible cause of the radiation induced softening (Zhao et al 1996). These results are in agreement with findings of Moreno et al (2006), El-Salhy et al (2006) and Lacroix et al (1990) in mango; Pimentel and Walder (2004) in banana and Singh and Pal (2007) and Singh and Pal (2009) in guava. Significantly better texture score was recorded at the full ripening stage in fruits stored at 12 0 C, ambient temperature and in CA (12 0 C) storage compared to fruits stored at 9 0 C temperature, which may be due to retardation of the biochemical changes and ripening process at desired temperature (Mane, 2009) and significantly decrease in texture during storage of fruits was due to changes in nature of pectin substances which cementing the cell wall and hydrolysis of starch, hemicelluloses and cellulose during ripening of fruit (Leopold, 1964).This finding is in conformity with the findings of Waskar and Masalkar (1997) in mango; Purvoko (2002) in banana.…”
Section: Texture Of Fruitsupporting
confidence: 88%
“…Several reports on irradiation have shown good response of mango to irradiation treatment. The response of mango fruit to irradiation depends upon cultivar, maturity status and post-harvest handling system (Akamine & Moy 1983;Boag et al 1990;Gonzalez-Aguilar et al 2001;Janave & Sharma 2005;Moreno et al 2006;Spalding & Von Windeguth 1988;Thomas 1986;Thomas & Janave 1975;Uthairatanakij et al 2006). Irradiation of mature green 'Alphonso' mangoes with a dose of 250 Gy delayed ripening to 16 days against 10 days in control as evidenced by fruit texture and skin colour (Dharkar et al 1966).…”
Section: Irradiationmentioning
confidence: 99%
“…However, a recent study has shown that skin and flesh colours of 'Nam Dokmai' and 'Chok Anan' mangoes were not affected by gamma irradiation at a dose level of 400 to 600 Gy (Uthairatanakij et al 2006). Recently, it has been reported that 'Tommy Atkins' mangoes can be irradiated with electron beam at 1 k Gy dose without having any adverse effect on biochemical and sensory attributes (Moreno et al 2006). The stage of maturation of mango fruit decides the rate of success as partially ripe fruit and those in their climacteric phase are largely unaffected by irradiation (Boag et al 1990).…”
Section: Irradiationmentioning
confidence: 99%
“…Nonetheless, irradiation caused detrimental effects on mango quality attributes (Cruz et al, 2012;M oreno et al, 2006 irradiation would differentially induce LD on different Australian mango cultivars. In addition, it was proposed that irradiation would inhibit skin degreening in mango.…”
Section: Research Approachmentioning
confidence: 99%